The Analysis of Economic Value on Irrigation Utilizationatrice Farming in Buahdua District, Sumedang Regency, West Java - Ulfah Suci Amalia; Ernah Ernah (Universitas Tadulako, 2017)
Water is a main factor on production input in rice farming. The need for water will increase as time progresses, but the availability of it is increasingly uncertain. One way to overcome the scarcity of water is the efficient using of water by determining the price of irrigation. This study aims to determine the price of water which is probably paid by farmers in rice farming, and to know the constraints faced by them. The research design used is quantitative descriptive. Primary data are obtained from 80 farmers taken by simple random sampling. Data analysis’ used here are analysis of descriptive, analysis of farming, and analysis of Willingness To Pay (WTP). The result of this research shows that the value of water rent in Buahdua Village is Rp. 4,428,031/ha/MT. Interviews show that almost all farmers are willing to pay the price of irrigation. The average value of PAP respondent is Rp. 61,813/ha/MT and the average value of TWTP is Rp. 28,751.891. Many obstacles faced by farmers in the use of irrigation is garbage, difficulty of getting water during the dry season, and damaged irrigation. This condition will affect the increasingly inefficient management of irrigation. Therefore, the economic value of water usage can be used as a reference asafees level by the farmers to reach efficiently.